2016
DOI: 10.3390/nu8010052
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Soy Product Supplemented with Isoflavones Improves the Lipid Profile of Moderately Hypercholesterolemic Men: A Randomized Controlled Trial

Abstract: Background: Cardiovascular disease is the leading cause of worldwide morbidity and mortality. Several studies have demonstrated that specific probiotics affect the host’s metabolism and may influence the cardiovascular disease risk. Objectives: The aim of this study was to investigate the influence of an isoflavone-supplemented soy product fermented with Enterococcus faecium CRL 183 and Lactobacillus helveticus 416 on cardiovascular risk markers in moderately hypercholesterolemic subjects. Design: Randomized p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 66 publications
(71 reference statements)
0
27
0
Order By: Relevance
“…A recent human clinical trial with isoflavone supplemented soy probiotic for 42 days, showed an improvement in the lipid profile of moderately hypercholesteremic men [42]. One major photochemical belonging to this group of soy isoflavones is genistein.…”
Section: Phytochemicals In Obesitymentioning
confidence: 99%
“…A recent human clinical trial with isoflavone supplemented soy probiotic for 42 days, showed an improvement in the lipid profile of moderately hypercholesteremic men [42]. One major photochemical belonging to this group of soy isoflavones is genistein.…”
Section: Phytochemicals In Obesitymentioning
confidence: 99%
“…The supplementation of soy product (equivalent of 10 10 CFU of probiotic strain) with 50 mg isoflavone per day for 42 days significantly improved the total cholesterol (TC), LDL-C (low-density lipoprotein-cholesterol) and electronegative LDL content in the subjects while the level of HDL-C (high-density lipoprotein-cholesterol) was unaffected and the level of fibrinogen and C-reactive protein levels were not enhanced. The results suggested that the consumption of probiotic soy product with isoflavone improved the cardiovascular risk factors in hypercholesterolemic subjects [24].…”
Section: Hypercholesterolemic Subjectsmentioning
confidence: 96%
“…Cavallini et al [24] studied the effect of probiotics (Enterococcus faecium CRL 183 and Lactobacillus helveticus 416) fermented soy product containing isoflavone on the lipid profile of moderately hypercholesterolemic male subjects. The supplementation of soy product (equivalent of 10 10 CFU of probiotic strain) with 50 mg isoflavone per day for 42 days significantly improved the total cholesterol (TC), LDL-C (low-density lipoprotein-cholesterol) and electronegative LDL content in the subjects while the level of HDL-C (high-density lipoprotein-cholesterol) was unaffected and the level of fibrinogen and C-reactive protein levels were not enhanced.…”
Section: Hypercholesterolemic Subjectsmentioning
confidence: 99%
See 2 more Smart Citations